ڕەنگدانەوەی نووسینە ڕۆژهەڵاتناسییەكان لە نووسینە مێژووییەكانی محەمەد ئەمین زەكی بەگدا - محمد, بهمن صاڵح; أحمد, سامان حسێن (Sulaimani Journal for Humanities, 2018)
Despite of the criticisms of orientalism and the attacks directed against it, one cannot deny its vital role in recording the history of the east and in developing a new academic method to approach oriental history. Additionally, oriental studies have had a great effect on the oriental historians themselves in terms of their style in documenting the history of the area. This effect can be clearly traced in the historical works of AmeenZeki Beg, a key Kurdish historian. Stemming from this view, this study specifically attempts to shed light on the effect of the orientalists and their historical products and references on Zeki Beg and his approach in recording the history of the Kurds. Moreover, this paper is composed of a number of sections. The first section presents a brief biography of Zeki Beg and his works. In the next section, the academic resources that played a role in recognizing Zeki Beg as a historian are covered. Section three places focus on the oriental studies’ effect on academic life of Zeki Beg. The fourth section deals with the way orientalism shaped this scholar. And in section five, the researcher sketches out the effect of oriental studies on theZekiBeg’s style in recording historical events. In the conclusion, a number of views are listed about such studies and how they referred to by Zeki Beg.